Expanding long-acting contraceptive options: a prospective cohort study of the hormonal intrauterine device, copper intrauterine device, and implants in Nigeria and Zambia. Issue 10 (October 2021) - Brunie, Aurélie; Stankevitz, Kayla; Nwala, Anthony Adindu; Nqumayo, Masauso; Chen, Mario; Danna, Kendal; Afolabi, Kayode; Rademacher, Kate H
Summary: Background: 30 years after the introduction of the levonorgestrel-releasing intrauterine device in Europe, several sub-Saharan African countries are seeking to broaden access to this contraceptive method. In this study, we aimed to assess 12-month continuation of the hormonal intrauterine device, copper intrauterine device, and implants, as well as to assess women's experiences and satisfaction using these methods in the private sector in Nigeria and the public sector in Zambia. Methods: We did a prospective cohort study of long-acting reversible contraceptive users across 40 private sector clinics in Nigeria and 21 public sector clinics in Zambia. Eligible women were aged 18–49 years in Nigeria and 16–49 years in Zambia, had chosen to receive the hormonal intrauterine device, copper intrauterine device, or implant (either a 5-year levonorgestrel-releasing subdermal implant or a 3-year etonogestrel-releasing subdermal implant), and, in Nigeria only, had access to a telephone. Women were interviewed within 100 days of receiving their contraceptive method either via telephone in Nigeria or in person in Zambia, with follow-up surveys at 6 months and 12 months. The primary outcomes were method-specific, 12-month continuation rates—ie, continuation rates of the hormonal intrauterine device, copper intrauterine device, and implant across Nigeria and Zambia. We used Kaplan-Meier methods to estimate the cumulative probabilities of method-specific continuation and a log-rank test to compare contraceptive methods. We analysed self-reported satisfaction and experiences as a secondary outcome. Findings: Between June 25 and Nov 22, 2018, we enrolled a total of 1542 women (n=860 in Nigeria and n=682 in Zambia) receiving a long-acting reversible contraceptive. In total, 835 women (266 [32%] hormonal intrauterine device users, 274 [33%] copper intrauterine device users, and 295 [35%] implant users) in Nigeria and 367 (140 [38%] hormonal intrauterine device users, 149 [40%] copper intrauterine device users, and 78 [21%] implant users) in Zambia were included in the study analysis. The 12-month cumulative continuation rates were 86·8% (95% CI 82·1–90·4) for the hormonal intrauterine device, 86·9% (82·1–90·4) for the copper intrauterine device, and 85·0% (80·2–88·7) for implants in Nigeria. In Zambia, the 12-month cumulative continuation rates were 94·7% (89·2–97·4) for the hormonal intrauterine device, 89·1% (82·3–93·4) for the copper intrauterine device, and 83·1% (72·2–90·1) for implants. At least 71% of respondents across the timepoints were very satisfied with their method, and at least 55 (79%) of 70 reported having recommended their contraceptive method to someone else. Across the methods, the most commonly self-reported positive aspect of long-acting reversible contraceptive use at 12 months was effectiveness in Nigeria (range 93–94%) and long-lasting duration in Zambia (48–60%). Between 124 (50%) of 248 and 136 (59%) of 230 Nigerian participants and 26 (42%) of 62 and 66 (57%) of 117 Zambian participants reported nothing negative about their contraceptive method. Interpretation: Our study showed high continuation rates and satisfaction across long-acting reversible contraceptives, including the hormonal intrauterine device, a method that has been largely underused in sub-Saharan Africa. This finding supports the inclusion of the hormonal intrauterine device as a valuable addition to the mix of contraceptive methods in Nigeria and Zambia. Funding: Bill & Melinda Gates Foundation.